Can coercion be justified when it benefits the poor? The case of commercial surrogacy industry in India - Asirvatham, Packiaraj (Bangladesh Journal of Bioethics, 2017)
Commercial surrogacy in India is a booming industry however the raising number of poor illiterate women's participation as commercial surrogate poses serious question of coercion, on the other hand it economically empowers them. In this context, this article analyses the crucial question, can coercion be justified when it benefits the poor by investigating commercial surrogates’ life stories and looking into the various types of coercion discreetly operates. It concludes with few recommendations which can help in empowering poor commercial surrogates who involved in commercial surrogacy industry in India.